Emerging therapeutic options for follicular-derived thyroid cancer in the era of immunotherapy - Turner, Naimah; Hamidi, Sarah; Ouni, Rim; Rico, Rene; Henderson, Ying C.; Puche, Maria; Alekseev, Sayan; Colunga-Minutti, Jocelynn G.; Zafereo, Mark E.; Lai, Stephen Y.; Kim, Sang T.; Cabanillas, Maria E.; et al. (Frontiers in Immunology, 2024)
Although most follicular-derived thyroid cancers are well differentiated and have an overall excellent prognosis following treatment with surgery and radioiodine, management of advanced thyroid cancers, including iodine refractory disease and poorly differentiated/undifferentiated subtypes, is more challenging. Over the past decade, better understanding of the genetic drivers and immune milieu of advanced thyroid cancers has led to significant progress in the management of these patients. Numerous targeted kinase inhibitors are now approved by the U.S Food and Drug administration (FDA) for the treatment of advanced, radioiodine refractory differentiated thyroid cancers (DTC) as well as anaplastic thyroid cancer (ATC). Immunotherapy has also been thoroughly studied and has shown promise in selected cases. In this review, we summarize the progress in the understanding of the genetic landscape and the cellular and molecular basis of radioiodine refractory-DTC and ATC, as well as discuss the current treatment options and future therapeutic avenues.